2021
DOI: 10.1086/711403
|View full text |Cite
|
Sign up to set email alerts
|

Curbing Shocks to Corporate Liquidity: The Role of Trade Credit

Abstract: Using data on exogenous liquidity losses generated by the fraud and failure of a cash-in-transit firm, we demonstrate a causal impact on firms' trade credit usage. We find that firms manage liquidity shortfalls by increasing the amount of drawn credit from suppliers and decreasing the amount issued to customers. The compounded trade credit adjustments are at least as great, if not greater than corresponding adjustments in cash holdings, suggesting that trade credit positions are economically important sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 47 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…Prior literature has suggested that trade credit is of a lower pecking order in external financing, which implies that companies that have difficulties financing through formal channels, such as bank loans, should have a higher propensity to use trade credit (Petersen and Rajan, 1997;Deloof and Jegers, 1999;Huyghebaert, 2006;Nilsen, 2002;Casey and O'Toole, 2014). Consistent with this view, Amberg et al (2021) present evidence that the demand for trade credit increases when firms face negative liquidity shocks due to bank fraud. Therefore, if trust indeed promotes access to trade credit, we should observe that, as the level of trust increases, the use of trade credit by financially constrained firms grows faster than that of unconstrained firms.…”
Section: Related Literature and Hypotheses Developmentsupporting
confidence: 71%
See 3 more Smart Citations
“…Prior literature has suggested that trade credit is of a lower pecking order in external financing, which implies that companies that have difficulties financing through formal channels, such as bank loans, should have a higher propensity to use trade credit (Petersen and Rajan, 1997;Deloof and Jegers, 1999;Huyghebaert, 2006;Nilsen, 2002;Casey and O'Toole, 2014). Consistent with this view, Amberg et al (2021) present evidence that the demand for trade credit increases when firms face negative liquidity shocks due to bank fraud. Therefore, if trust indeed promotes access to trade credit, we should observe that, as the level of trust increases, the use of trade credit by financially constrained firms grows faster than that of unconstrained firms.…”
Section: Related Literature and Hypotheses Developmentsupporting
confidence: 71%
“…For example, modern economic factors, such as economic development stage and institution quality, might codetermine 1 In addition, the Bank for International Settlements (BIS) estimates that the volume of trade payables amounts to approximately one third of the outstanding bank loans of non-financial companies in European countries, the US and Turkey as of 2018. At the macro level, an active line of research suggests that nonfinancial firms function as financial intermediaries through trade credit provisions (Demirgüç-Kunt and Maksimovic, 2001;Amberg et al, 2021), which promotes economic growth (Fisman and Love, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amberg et al. (2021) use a plausibly exogenous shock to liquidity demand for firms; they find that this shock leads to an increase in the use of trade credit and a decline in firms' cash accumulation. To satisfy this increased demand for trade credit financing, more trade credit needs to be extended.…”
Section: Empirical Strategymentioning
confidence: 99%